Stem and Fruit Canker of Dragon Fruit in South Florida - Cheng-Fang Hong; Shouan Zhang; Romina Gazis; Jonathan H Crane; Jeff Wasielewski (EDIS, 2020)
Dragon fruit, also known as pitahaya, pitaya, and strawberry pear, is a group of vine-like, climbing cacti. In south Florida, production of dragon fruit has been steadily increasing since the 2000s, and growers in Florida consider dragon fruit as a potential alternative fruit crop to avocado and citrus, two economically important fruit crops largely impacted by laurel wilt and huanglongbing, respectively. This new 4-page article focuses on the symptomology and epidemiology of stem and fruit canker, a prevailing disease on dragon fruit. Suggested management strategies for the disease are also discussed based on recent studies conducted in south Florida. Written by Cheng-Fang Hong, Shouan Zhang, Romina Gazis, Jonathan H. Crane, and Jeff Wasielewski, and published by the UF/IFAS Plant Pathology Department. https://edis.ifas.ufl.edu/pp355